Qualitative structure-activity relationships of the major tyrocidines, cyclic decapeptides from Bacillus aneurinolyticus - Spathelf, Barbara Marianne (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Biochemistry))--University of Stellenbosch, 2010.